Unexplained mysteries of World War II - Jackson, Robert (Gallery Books New York, 1991)
The many facts surrounding the Unexplained Mysteires of world War II are supported by a wealth of fascinating historical maps and photographs.
Keywords: Miscellanea -- 1939-1945